Transient Magnetohydrodynamic Free Convective Heat and Mass Transfer Flow with Thermophoresis past a Radiate Inclined Permeable Plate in the Presence of Variable Chemical Reaction and Temperature Dependent Viscosity - Alam, M. S. S.; Rahman, M. M. M.; Sattar, M. A. A. (Nonlinear Analysis: Modelling and Control, 2009)
In the present study, an analysis is carried out to investigate the effects of variable chemical reaction, thermophoresis, temperature-dependent viscosity and thermal radiation on an unsteady MHD free convective heat and mass transfer flow of a viscous, incompressible, electrically conducting fluid past an impulsively started infinite inclined porous plate. The governing nonlinear partial differential equations are transformed into a system of ordinary differential equations, which are solved numerically using a sixth-order Runge-Kutta integration scheme with Nachtsheim-Swigert shooting method. Numerical results for the non-dimensional velocity, temperature and concentration profiles as well as the local skin-friction coefficient, the local Nusselt number and the local Stanton number are presented for different physical parameters. The results show that variable viscosity significantly increases viscous drag and rate of heat transfer. The results also show that higher order chemical reaction induces the concentration of the particles for a destructive reaction and reduces for a generative reaction.